A note on the comparison between laplace and Sumudu transforms. - Kilicman, Adem; Eltayeb, Hassan; Mohd Atan, Kamel Ariffin (Iranian Mathematical Society, 2011)
In this paper, we discuss the existence of double Sumudu transform and study relationships between Laplace and Sumudu transforms. Further, we apply two transforms to solve linear ordinary differential equations with constant coefficients and non constant coefficients.